GENERAL DIRECTIONS OF DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN THE CONTEXT OF INDUSTRY 4.0 - VILIANSKYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The need for rapid identification of problems with simultaneous production of necessary corrective actions, which are aimed at optimizing the performance of the entire production system substantiates the relevance of research into the effectiveness of the introduction of Industry 4.0 technologies in industry. The article reviews analytical studies of the concept of “Industry 4.0” in foreign scientific literature, as well as a comparative analysis of the main characteristics of Industry 3.0 to Industry 5.0. in order to identify the characteristics and distinctions between them and from related concepts such as “4th industrial revolution”, “cyber-physical systems”, “Internet of Things”. The main key success factors of digitalization are identified as people, strategy, technology, which will allow the development of intelligent algorithms to improve operational efficiency; contribute to the efficient use of resources, reduce the cost of product quality, the introduction of automation; contribute to improving the economy and productivity of operations. The main directions of influence of Industry 4.0 technologies on the efficiency of industrial enterprises are presented. It is concluded that the application of digital technologies of Industry 4.0 provides an opportunity for large-scale technological transformation of production, and is aimed at increasing the innovative potential of industrial enterprises. In addition, the features of competition for technology, investments, markets, territories of productive forces location are emphasized. It also emphasizes the main “revolutionary” trends in industrial development associated with the launch of innovation and technology cycle initiated by Industry 4.0.
Keywords: Industry 4.0; digital technologies; innovation; manufacturing enterprises; digitalization; productivity